(untitled) (Web of Teachers: Inderscience Research, 2024)
Physique of science hard the body mechanic properties, mechanical stress relative to lengthen dependence in explanation very efficient method is considered Mechanic voltage relative to prolong connection graph student and in explaining to students much to difficulties occurs . This is the method using of students creative thinking by increasing good to understanding have to be provides. Physics in science applied another of the methods different side this method students with the help of animated graphics seeing thinking the ability increases.